Mechanic's Hands and Drug Eruption to Hydroxychloroquine: Precious Diagnostic Tools - Maria Mendonça Sanches; Rita Pimenta; Inês Cordeiro; Bernardo Baptista (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
The clinical diagnosis of dermatomyositis can be difficult and challenging. In the right clinical setting and with the use of the recently described myositis specific antibodies, an earlier diagnosis can be made and therapeutic approaches promptly started, minimizing the risk of disease progression. We herein present a case of a patient with mechanic's hands and a previously documented drug eruption to hydroxychloroquine. Although these clinical findings are not pathognomonic of dermatomyositis, in the right clinical scenario, they are precious diagnostic tools.